Radiation protection considerations with [89Zr]Zr-girentuximab PET and surgery - Adnan Chowdhury; Clément Morgat; Clement Bailly; John Sunderland; Stephen A. Graves; Andrew M. Scott; Sean Baker; Beverley F. Holman (EJNMMI Research)
Abstract Background 89Zr is emerging as a popular positron-emitting radionuclide for imaging; however, its 909 keV gamma emission presents shielding challenges, and radiation exposure safety guidelines for healthcare professionals working with the radionuclide have not been well-established. To guide assessment of the radiation risk and necessary safety guidelines, we present laboratory dose rate measurements of 89Zr syringes and vials, and dose rates measurements made during the ZIRCON clinical trial ([89Zr]Zr-girentuximab) to evaluate healthcare provider exposure during administration, imaging, and surgical procedures. Results The maximum dose rate from a vial with no shielding was 0.334 µSv/h/MBq, and the minimum dose rate with 66 mm lead shielding was 0.004 µSv/h/MBq. The controlled spill measured 0.52 µSv/h/MBq. Dose rates 1 m from patients who received [89Zr]Zr-girentuximab had an average of 3.90 µSv/h at imaging. During surgery, waste measured below background levels, and a bed assistant 0.8 m from the patient received a 5 µSv/h whole-body dose rate. The excised kidney measured 6 µSv/h at 5 cm. Conclusions Our results demonstrate low radiation exposure levels associated with 89Zr handling and exposure to the patient. With potential integration of 89Zr into clinical practice, appropriate radiation safety guidelines are needed. Dose rate measurements can help guide development of best practices and site-specific protocols. Clinical trial number: not applicable for this study; ZIRCON trial number NCT03849118, registered on 19 February 2019.